# Step-by-step Solution

## Solve the equation $\frac{x+1}{2}-\frac{2-x}{3}=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x=\frac{1}{5}$

## Step-by-step explanation

Problem to solve:

$\frac{x+1}{2}-\frac{2-x}{3}=0$
1

Multiply the fractions by the least common multiple of the denominators, which is $6$

$\frac{6\left(x+1\right)}{2}+\frac{-6\left(2-x\right)}{3}=0$
2

Take $\frac{6}{2}$ out of the fraction

$3\left(x+1\right)+\frac{-6\left(2-x\right)}{3}=0$
3

Take $\frac{-6}{3}$ out of the fraction

$3\left(x+1\right)-2\left(2-x\right)=0$
4

Solve the product $3\left(x+1\right)$

$3x+3-2\left(2-x\right)=0$
5

Solve the product $-2\left(2-x\right)$

$-1+3x+2x=0$
6

Adding $3x$ and $2x$

$5x-1=0$
7

Subtract $-1$ from both sides of the equation

$5x=1$
8

Divide both sides of the equation by $5$

$x=\frac{1}{5}$

$x=\frac{1}{5}$

### Problem Analysis

$\frac{x+1}{2}-\frac{2-x}{3}=0$

Equations

~ 0.08 seconds